2014
DOI: 10.1177/230949901402200217
|View full text |Cite
|
Sign up to set email alerts
|

Modified Weaver-Dunn Procedure versus the Use of a Synthetic Ligament for Acromioclavicular Joint Reconstruction

Abstract: PURPOSE. To compare the subjective outcome of acromioclavicular joint (ACJ) reconstruction using the modified Weaver-Dunn procedure versus the Surgilig synthetic ligament. METHODS. 55 patients aged 19 to 72 (mean, 42) years underwent ACJ reconstruction of Rockwood grade 3 (n=38), grade 4 (n=8), and grade 5 (n=9) using the modified Weaver-Dunn procedure (n=31) or the Surgilig synthetic ligament (n=24), based on the surgeon's preference. The mean period from injury to surgical treatment was 39 months. Subjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 29 publications
1
58
0
Order By: Relevance
“…Debski et al 12 proved the conoid ligament restrains the movement against anterosuperior force of clavicle and the trapezoid ligament against the posterior force of clavicle. The Weaver-Dunn and Bosworth techniques, with their various modifications, are currently the most popular procedures in use 13,14 , alongside various fixation methods, like screws, pins, hook plates. Recently, hook plate is widely used.…”
Section: Discussionmentioning
confidence: 99%
“…Debski et al 12 proved the conoid ligament restrains the movement against anterosuperior force of clavicle and the trapezoid ligament against the posterior force of clavicle. The Weaver-Dunn and Bosworth techniques, with their various modifications, are currently the most popular procedures in use 13,14 , alongside various fixation methods, like screws, pins, hook plates. Recently, hook plate is widely used.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many have recommended augmentation procedures to protect the transferred CA ligament. Modifications of the WD procedure have achieved good outcome for acute and chronic AC joint dislocations [ 28 - 31 ]. A biomechanical studies concluded that the CA ligament has only 30% of the strength and 10% of the stiffness of the intact ligaments, and failures occur mainly at the suture that attaches the transferred CA ligament [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Modified WD method involved excision of the distal end of the clavicle and transferring of the CA ligament to the distal end of the clavicle, using the ligament as a substitute for the ruptured CC ligament with augmentation of the transposed CA ligament by either cerclage wires, [ 24 ] screw fixation, [ 12 ] autogenous fascia lata graft, [ 25 ] or synthetics such as GORE-TEX, [ 26 ] Dacron, [ 27 ] carbon fibers, [ 28 ] and braided polyester [ 29 ]. Recently the modified WD procedure was compared with synthetic ligament and Graft Ropet (Arthrex, Naples, FL) reconstruction in both clinical and biomechanical studies revealing inferior results [ 30 , 31 ]. It seems that while most nonanatomic techniques were able to restore vertical stability at the AC joint they still were significantly lacking in anteroposterior anatomic reconstruction of the CC ligaments [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…60 When comparing the modified Weaver-Dunn procedure to synthetic ligaments for the treatment of chronic dislocations, the synthetic ligament resulted in better outcome scores as well as earlier return to work and sport. 71 In a systematic review by Borbas et al tendon or ligament transfers, such as the Weaver-Dunn procedure, showed inferior clinical and radiological outcomes when compared to non-biological (e.g. synthetic ligaments and suture loops) and biological (e.g.…”
Section: Ligament and Tendon Transfersmentioning
confidence: 99%